Improving Students’ Speaking Ability Through Drama Performance at the Eleventh Grade of SMA N 17 Medan - Pasaribu, Mey Diana (Pascasarjana Universitas HKBP Nommensen, 2023)
This study deals with the improving students’ speaking ability through drama performance at the eleventhgrade of SMA N 17 Medan. The main objective of this study is to describe the implementation of dramaperformance in teaching speaking. The sample of this study was 50 students in class XI IS-1. This studywas conducted by using classroom action research. The research was conducted in two cycles, cycle Iconsisted of three meetings, and cycle II consisted of three meetings. The instruments for collecting thedata were quantitative data (speaking test), and qualitative data (interview and observation sheet). Basedon speaking scores in quantitative data, students’ score improve continuously. Based on interview andobservation sheet from qualitative data, it was found that the students were active, interested, andenthusiastic in speaking especially through drama performance. The result of the research showed thatdrama performance significantly improved students’ achievement in speaking ability.